The complete mitochondrial genome of Dysgonia stuposa (Lepidoptera: Erebidae) and phylogenetic relationships within Noctuoidea - Yuxuan Sun; Yeshu Zhu; Chen Chen; Qunshan Zhu; Qianqian Zhu; Yanyue Zhou; Xiaojun Zhou; Peijun Zhu; Jun Li; Haijun Zhang (PeerJ, 2020)
To determine the Dysgonia stuposa mitochondrial genome (mitogenome) structure and to clarify its phylogenetic position, the entire mitogenome of D. stuposa was sequenced and annotated. The D. stuposa mitogenome is 15,721 bp in size and contains 37 genes (protein-coding genes, transfer RNA genes, ribosomal RNA genes) usually found in lepidopteran mitogenomes. The newly sequenced mitogenome contained some common features reported in other Erebidae species, e.g., an A+T biased nucleotide composition and a non-canonical start codon for cox1 (CGA). Like other insect mitogenomes, the D. stuposa mitogenome had a conserved sequence ‘ATACTAA’ in an intergenic spacer between trnS2 and nad1, and a motif ‘ATAGA’ followed by a 20 bp poly-T stretch in the A+T rich region. Phylogenetic analyses supported D. stuposa as part of the Erebidae family and reconfirmed the monophyly of the subfamilies Arctiinae, Catocalinae and Lymantriinae within Erebidae.